Implementing Group Nutrition Education in Ogden, Kansas - Bono, Erika (My University, 2013)
Kansas State Research and Extension receives federal funding to provide nutrition education programs for limited resource families. One such program is the Expanded Food and Nutrition Education Program (EFNEP) which targets main food providers in limited-resource households in order to assist in positive changes in diet and health behaviors of family units for improved “nutritional well-being”. Traditionally, EFNEP delivers ten to twelve lessons in a series, but funding and time burdens could be attenuated with fewer lessons if similar outcomes were observed in health behavior changes. Two, four-week adult sessions were held at the Ogden Community Center. Classes met once a week. 24-hour diet recall and behavioral checklists were completed by participants at entry and exit in both sessions. For the first session, a one-month follow up recall and checklist were completed via mail. Evaluation of entry, exit, and session one follow-up data suggest that minimal to no behavioral change is apparent after the four-week session, but positive behavior changes (such as an increase in vegetable intake) was observed when reviewing follow up data. This suggests that four weekly classes are insufficient for immediate behavior change, but may contribute to behavior changes in the future. These results can be used as preliminary support for further observance of the potential short and long-term health behavior outcomes that can come from offering abbreviated EFNEP programs.
Keywords: Public Health; Group Nutrition; EFNEP; Public Health (0573)